Censorship detected in ET (Ethiopia) - Voidly (2026)
CRITICAL severity censorship detected in Ethiopia. Confidence: 78%. Data sourced from OONI.
Censorship Incident ID: ET-2026-0707
Keywords: censorship; ET; censorship; critical